Protection of Property by Means of Criminal Law in Ukraine During the ix-the End of XIX Century: Historical Aspects - Стрельцов, Євген Львович; Стрельцов, Є. Л.; Стрельцов, Евгений Львович; Streltsov, Yevhen L.; Соловйова, Аліна Миколаївна; Соловйова, А. М.; Соловьева, Алина Николаевна; Soloviova, Alina M. (Prague, 2020)
The article analyzes legal protection of property rights under the laws on Ukrainian lands. The author explores the point of view of several scientists who were contemporaries of the laws. The present study aims to investigate the legal dimensions of property crimes towards the concept of crimes against property. The study has concluded that there have been lots of impacts on Ukrainian legal tradition. Therefore, there is no linearity in the development of criminal law norms throughout the territory of Ukraine.

У статті проаналізовано правовий захист права власності відповідно до українських законів. Автор досліджує точку зору кількох вчених, які були сучасниками законів. Дане дослідження має на меті дослідити правові аспекти майнових злочинів по відношенню до поняття злочинів проти власності. Дослідження дійшло висновку, що на українську правову традицію був чималий вплив. Тому не існує лінійності у розробці кримінально-правових норм на всій території України.

В статье проанализирована правовая защита права собственности в соответствии с украинскими законами. Автор исследует точку зрения нескольких ученых, которые были современниками законов. Данное исследование имеет целью исследовать правовые аспекты имущественных преступлений по отношению к понятию преступлений против собственности. Исследование пришло к выводу, что на украинскую правовую традицию осуществлялось множественное влияние. Поэтому не существует линейности в разработке уголовно-правовых норм на всей территории Украины.
Streltsov Ye. Protection of Property by Means of Criminal Law in Ukraine During the ix-the End of XIX Century: Historical Aspects / Ye. Streltsov, A. Soloviova // The Lawyer Quarterly : International Journal for Legal Research . – V. 10 (3). – Prague, 2020. – P. 337–345.
Keywords: crime; theft; robbery; property; property damage; злочин; крадіжка; пограбування; майно; майнова шкода; преступление; кража; грабеж; имущество; материальный ущерб; Research Subject Categories::LAW/JURISPRUDENCE